Right of the disabled person for employment: a comparative study between Malaysia and the United Kingdom / Amizatul Izzati Johari …[et al.] - Johari, Amizatul Izzati; Ahmad, Nashuha Nardhiyah; Husin, Fasiha Hadana; Md. Khusairi, Nursyifa; Khalid, Nurul Ain (2014)
In Malaysia, rights of Persons with disabilities (PWDs) are protected under the Persons with Disabilities Act 2008. This Act however is not adequate enough to protect PWDs in the world of employment compared to the law in the United Kingdom (UK). Therefore, this paper aims to examine and understand the challenges that are encountered by Malaysians with disabilities in the world of employment. Section 29 of the Persons with Disabilities Act 2008 laid down the right to equal employment. Unfortunately, it is ineffective, as the Act does not include punishment for breaching its provisions. This PWDs Act 2008 can be regarded as merely rhetoric without effective enforcement mechanism. Meanwhile, in UK, Equality Act 2010 prohibits discrimination by employers against existing or prospective employees on the ground of disability. It protects applicants for employment and those already in employment. The comparison between Malaysian position and UK position on the protection of the rights of PWDs in employment can be seen in term of the gaps of PWDs Act 2008 and the UK law, which are Equality Act and Disability Discrimination Act 1995. There are several recommendations to ensure the equitable right for PWDs as well as improving employment opportunities for PWDs in Malaysia.